IMPLEMENTASI MODEL PEMBELAJARAN JIGSAW UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Parsyah, Ananda; Hadiansah, Dede; Rukmini, Piyantina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by low student motivation and learning outcomes that failed to meet the minimum mastery standards. The objective was to examine the implementation of the Jigsaw learning model in enhancing student motivation and learning outcomes in the Natural and Social Sciences (IPAS) subject for fourth-grade students at SD Negeri 1 Benda. The study employed a Classroom Action Research (CAR) method conducted over two cycles, with each cycle comprising planning, implementation, observation, and reflection stages. The research subjects consisted of 30 fourth-grade students. Data collection instruments included teacher activity observation sheets, learning motivation questionnaires, and learning outcome tests. Data were analyzed using both quantitative and qualitative descriptive methods. Student learning motivation reached 74.7% in Cycle 1 and rose to 94% in Cycle 2, indicating increased positive engagement. Regarding learning outcomes, Cycle 1 results showed that 16 students (53%) achieved mastery, while 14 students (47%) did not. In Cycle 2, 27 students (83%) achieved mastery, and only 3 students (17%) did not. These findings demonstrate that student learning outcomes in the IPAS subject improved progressively across cycles with the application of the Jigsaw model; by Cycle 2, outcomes surpassed the established target of 80%. Thus, it can be concluded that the Jigsaw learning model is effective in enhancing student motivation and learning outcomes in the IPAS subject for fourth-grade elementary students.